A Hydrogen Pressure Sensor based on Bulk-micromachined Silicon Strain Gauges. (2016) - Kim, Jinwoong; Kim, Kibeom; Ham, Seung Woo; Bae, Nam-Ho; Park, Myung Kyun; Min, Nam Ki
Abstract: In this article, we report on the new design of a miniaturized silicon strain gauge and its application to hydrogen pressure sensor. The bulk-micromachined silicon gauges have the through holes and the closed structure, unlike the current competitive devices with open structure. This unique design concept reduces shifting or rotation of gauge position during glass frit bonding and enables the automation of alignment and bonding processes, which improves the sensor performance and yield and hence reduces sensor cost. The prototype pressure sensors tested under pressure ranging from 0 to 50bar at different temperature have a linear output with a typical sensitivity of about 0.72mV/V/bar(before calibration) and 16mV/V/bar(after calibration), and a calibrated offset drift of –6mV to 2mV.